Research for Practice: Cluster Scheduling for Datacenters. - SCHWARZKOPF, MALTE (Communications of the ACM, 2018)
The article summarizes several articles presenting research on the use of distributed cluster scheduling for datacenters. Articles cited include "Large-Scale Cluster Management at Google With Borg" by A. Verma, et al. in the publication "Proceedings of the 10th European Conference on Computer Systems"; "Mesos: A Platform for Fine-Grained Resource Sharing in the Datacenter" by B. Hindman, et al. in the publication "Proceedings of the Usenix Conference on Networked Systems Design and Implementation:; and "Sparrow: Distributed, Low-Latency Scheduling" by K. Ousterhout, et al. in the publication "Proceedings of the Symposium on Operating Systems Principles."